Summertime : let's look at the seasons - Schweninger, Ann (New York : Scholastic Inc, 1992)
It's Hot! What do you do in the summer? Go to the beach? Sit in the shade? Make ice pops? run from the rain?
Keywords: Summer -- Fiction; Children stories -- Fiction